Unlocking resilience and sustainability with earth-based materials: a principled framework for urban transformation - Bühler, Michael; Hollenbach, Pia; Köhler, Lothar; Armstrong, Rachel (Frontiers in Built Environment, 2024)
This paper introduces a transformative 'living' hypothesis in architecture and engineering, proposing a paradigm shift from conventional design to regenerative, ecologically interconnected resilient systems. At the heart of our hypothesis is the integration of earth-bound materials and bioreceptive surfaces through metabolic exchanges that can be directly monitored via bioelectricity using advanced computational models and cooperative governance structures. This innovative approach that links the living world with natural materials and digital computing, aims to foster sustainable urban development that dynamically and meaningfully responds to ecological shifts, thereby enhancing social sustainability and environmental resilience.Founded on an active relationship with Earth Based Materials (EBMs) our work operationalises the foundational link between organic life and inorganic matter, e.g., minerals, to establish a dynamic relationship between building materials, and ecological systems drawing on the foundational metabolisms of microbes.To enable this ambitious synthesis, our work builds upon and diverges from traditional foundations by operationalizing actor-network theory, new materialism, and regenerative design principles through the application of bioelectrical microbes to 'living' materials and digital twins. We propose a novel resilience framework that not only advocates for a symbiotic relationship between human habitats and natural ecosystems but also outlines practical pathways for the creation of adaptive, self-organizing built environments that are informed by data collection and metabolic feedback loops. These environments are fundamentally regenerative, dynamic, and environmentally responsive in ways that can be understood and engaged by human engineers and designers, transcending current sustainability and resilience targets through a methodology rooted in interdisciplinary collaboration.We address challenges such as regulatory barriers, lack of standardization, and perceptions of inferiority compared to conventional materials, proposing a new standardization framework adaptable to the unique properties of these materials. Our vision is supported by advanced predictive digital modelling techniques and sensors, including the integration of biofilms that generate action potentials, enabling the development of Digital Twins that respond to metabolic signals to enhance sustainability, biodiversity, and ultimately generate environmentally positive socio-economic outcomes.This paper reviews existing methodologies to establish an overview of state-of-the-art developments and offers a clear, actionable plan and recommendations for the realization of regenerative and resilient systems in urban development.